Implementasi Faktor-faktor Berpengaruh Terkait Efisiensi dan Kredibilitas Bank umum Syariah di Indonesia - Erna Wahyu Setiyaningsih; Irfa Febriyani; Sabrina Sukma Maulidya; Marlinda Effendi; Marfita Hikmatul Aini; Muhammad Taufiq Abadi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Sharia banks are financial institutions that don’t actually rely on interest to function. In other words, Sharia Bank is a financial institution whose main business is providing financing and other services in payment traffic and money circulation whose operations are adjusted to the principles of Islamic law. Sharia Bank itself, commonly known as an Interest-Free Bank, is a financial/banking institution whose operations and products are developed based on the Al-Quran and the Hadith of the Prophet SAW. Islamic banks do their businesses without using the interest system. The problem of the contradiction between interest and usury can be resolved alternatively by using the existence of sharia banks/Islamic banks. The Idea of “sharia banking” generally proposes an economic structure that is in harmony Keywords: Islamic Banking, Profit Sharing, Islamic Economics.